THE ISLAMIZATION OF THE MALAY ARCHIPELAGO IN OTTOMAN MANUSCRIPTS - Alaeddin Tekin (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2024)
The Ottoman archives possess one of the most extensive collections globally. With its repository of 95 million documents, it stands out as a rare archive that not only illuminates the Ottoman Empire but also contributes to the broader scope of world history. Within the Ottoman archives, numerous documents pertain to the Malay World, predominantly encompassing the colonial occupations within the region and diplomatic endeavours undertaken by the Ottoman Caliphate. Each of these documents has been meticulously examined, unearthing original insights into the propagation of Islam in the Malay Archipelago. Among these insights are correspondences dispatched by regional sultans to stanbul, while a significant portion emerges from research conducted by Ottoman-appointed consuls in the archipelago. This study’s central aim revolves around assessing the progression of Islam into the Malay Archipelago—a region housing the world’s most densely populated Muslim community—using resources within the Ottoman archives.